Disordered rock salt cathode material and manufacturing method thereof

By using metal precursor compounds in lower oxidation states to form an improved disordered rock salt structure, the problem of poor conductivity of disordered rock salts is solved, the high energy density and cycle life are improved, and the performance of lithium-ion batteries is significantly improved.

CN119183440APending Publication Date: 2024-12-24WILDCAT DISCOVERY TECHNOLOGIES INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380040562.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-03
Filing Date
2023-06-01
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

The disordered rock salt structure, as a cathode material for lithium-ion batteries, has poor conductivity, which limits the improvement of its energy density and cycle life.

Method used

By using metal precursor compounds in lower oxidation states, such as Mn with an oxidation state of 2, an improved disordered rock salt structure is formed, and disordered rock salts with small particle size and high metal redox capacity are formed by heating treatment, thereby improving their conductivity and cycle life.

Benefits of technology

A higher metal redox capacity and oxygen redox capacity than traditional materials are achieved, which significantly improves the energy density and cycle life of the battery, and achieves relatively high energy density under lower cost raw material conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119183440A_ABST
    Figure CN119183440A_ABST
Patent Text Reader

Abstract

It has been found that an improved disordered rock salt consisting of Mn is produced by a method comprising mixing a lithium compound with a metal precursor compound consisting of Mn in the oxidation state of 2 to form a mixture, and then heating the mixture to a temperature to form a disordered rock salt structure. The method can achieve improved cycle life by altering the metal and oxygen redox of the disordered rock salt.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of batteries. Background Art

[0002] Lithium metal oxides have been used to formulate cathode materials for lithium-ion batteries. The cathodes are derived from several basic crystal structure types, such as spinel, olivine, and layered oxide structures. Layered oxide structures include lithium-excess type structures, in which extra lithium is present in the structure.

[0003] Recently, attention has focused on disordered rock salt structures, such as those formed from certain lithium metal oxides. A compound represented by the formula:

[0004] xLi3NbO4 • (1-x)LiMO2(1)

[0005] Where M is a divalent or trivalent cation, it has been shown to be a promising class of transition metal oxides for use as cathodes in lithium-ion batteries. Compounds of formula (1) are considered to be disordered rock salts in which random atomic arrangements of lithium and transition metal ions are stacked in a close-packed cubic structure. These disordered rock salt compositions offer the ability to contain up to 3 lithium atoms per molecular formula unit, which is more than conventional excess lithium layered materials. Formula (1) can be converted and represented as Li x M y N z O w .

[0006] Disordered rock salt structures are attractive cathode materials for next-generation lithium-ion batteries because they have higher specific energy density (e.g., higher theoretical energy density) than state-of-the-art cathode materials such as layered lithium metal oxide structures. For example, the theoretical gravimetric energy density of some disordered rock salt structure materials is about 1120 Wh / kg, while the theoretical gravimetric energy density of LiMn2O4 active materials is about 492 Wh / kg, and LiMn 1.5 Ni 0.5 The theoretical gravimetric energy density of O4 is about 691 WHO / kg. This energy density is particularly attractive when using lower cost raw materials as components of the disordered rock salt structure (such as manganese). Therefore, disordered rock salt materials can achieve relatively high energy density at relatively low material cost. In order to achieve comparable energy density, known cathode materials require higher cost raw materials, such as cobalt or nickel.

[0007] The challenge of disordered rock salt materials is their relatively poor electrical conductivity. Reducing the particle size of disordered rock salt by grinding and then reaggregating the ground particles has been described to improve conductivity by shortening the electron and ion transport paths (U.S. Patent Publication No. 2022 / 0059816). Summary of the invention

[0008] It has been found that improved disordered rock salt materials can be formed by using metals in precursor compounds that are in a lower oxidation state before heating. The mechanism is not entirely clear. It has been found that, other variables being equal, the particle size or crystal size of the particles formed is smaller than the particle size or crystal size of the particles formed using precursor compounds with metals in a higher oxidation state.

[0009] For example, the method includes mixing a lithium compound with a metal precursor compound consisting of Mn in an oxidation state of 2 to form a mixture, and then heating the mixture to a certain temperature to form a disordered rock salt structure. Mn in an oxidation state of 2 can also be formed as follows. In the absence of a lithium compound, a mixture consisting of a Mn compound having an oxidation state greater than 2 and at least one other metal precursor compound is formed at a temperature at which a precursor (also referred to as an intermediate precursor) is formed. This intermediate precursor formed consists of Mn in a reduced oxidation state of 2. The resulting intermediate precursor can then be mixed with a lithium source and heated to form a disordered rock salt.

[0010] The method can produce disordered rock salt with metal redox capacity and oxygen redox capacity, wherein the metal redox capacity is greater than the oxygen redox capacity. Similarly, the method can produce disordered rock salt with metal redox capacity, which is at least partially due to the presence of Mn in the 2+ valence state of reduction, and it is believed but not limited thereto, which may contribute to improving metal redox capacity and improving cycle life. For example, the method can be capable of forming a disordered rock salt composed of Li, Mn and O, wherein at least 1 mol% of Mn is in the 2+ valence state. The valence state of Mn and the ratio in the 2+ valence state can be determined by known methods, such as the X-ray absorption spectroscopy described in Phys. Rev. B 94, 155117, October 12, 2016. Ideally, at least 2%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40% or 50% of the Mn present in the disordered rock salt is substantially all in the 2+ valence state.

[0011] The disordered rock salt can be used as an electrode of an electrochemical cell. The disordered rock salt material can be used to form a cathode. The electrochemical cell utilizing the disordered rock salt material can be a primary lithium ion battery or a secondary lithium ion battery. The lithium ion battery is ideally a secondary battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 is an X-ray diagram of the intermediate oxide used in the process of the present invention.

[0013] Figure 2 is a scanning electron micrograph (SEM) of the disordered rock salt of the present invention.

[0014] Figure 3 This is a SEM of a disordered rock salt not of the present invention.

[0015] Figure 4 It is the X-ray diffraction diagram of the disordered rock salt of the present invention and the disordered rock salt not of the present invention.

[0016] Figure 5 1 is the initial charge and discharge curve of the battery cell using the disordered rock salt of the present invention.

[0017] Figure 6 The figures show the capacity and cycle of a battery cell using the disordered rock salt of the present invention and a battery cell using the disordered rock salt not of the present invention. DETAILED DESCRIPTION

[0018] The following definitions apply to some aspects described with respect to some embodiments of the present invention. These definitions may also be expanded upon herein. Each term is further explained and illustrated by the description, drawings, and examples. Any interpretation of the terms in this specification should take into account the complete description, diagrams, and examples provided herein.

[0019] The singular terms "a", "an" and "the" include plural references unless the context clearly dictates otherwise. Thus, for example, reference to one item may include plural items unless the context clearly dictates otherwise.

[0020] Rate "C" means (depending on the context) a fraction or multiple of the discharge current relative to the "1 C" current value (at which the battery (in a substantially fully charged state) will be substantially fully discharged in one hour), or a fraction or multiple of the charge current relative to the "1 C" current value (at which the battery (in a substantially fully discharged state) will be substantially fully charged in one hour).

[0021] To the extent that certain battery characteristics vary with temperature, those characteristics are specified at 30 degrees Celsius unless the context clearly dictates otherwise.

[0022] Ranges presented herein include their endpoints. Thus, for example, a range of 1 to 3 includes the values ​​1 and 3 and intermediate values.

[0023] In disordered rock salt compositions, both lithium and transition metals occupy a cubic close-packed lattice of octahedral sites. In electrochemical reactions, lithium diffusion occurs by lithium jumping from one octahedral site to another via an intermediate tetrahedral site. The lithium in the intermediate tetrahedral site is the activated state in lithium diffusion. The activated tetrahedral lithium ion shares faces with the following four octahedral sites: (i) a site previously occupied by the lithium ion itself; (ii) a vacancy that the lithium ion will enter; and (iii and iv) two sites that can be occupied by lithium, a transition metal, or a vacancy.

[0024] The method can be used to make any disordered rock salt, such as rock salts known in the art that can be used to make battery cathodes composed of Mn (e.g., U.S. Patent No. 10,280,092). The method can use longer annealing times, but produce disordered rock salt particles that are equally small or smaller. For example, all other conditions being equal, the method achieves the same or smaller grain or particle size as a method that does not use a manganese + 2 precursor compound, even if the heating time is longer (i.e., 2, 5, or 10 times at the same temperature). This provides a more robust method for forming disordered rock salts.

[0025] Exemplary disordered rock salts can be any rock salt containing Mn, such as the rock salts described in U.S. Application No. 15 / 222,377 (now U.S. Patent No. 10,280,092), which is incorporated herein by reference in its entirety. Other disordered rock salts such as those described in U.S. Patent Nos. 10811671, 9692043, 9093712, 9083062, 8722250, 8535832, 10833322, 10497928, 9865872, and 9780363 may be useful when they are composed of Mn and are incorporated herein by reference. The disordered rock salt composition typically includes lithium, transition metals, and oxygen. One or more transition metals or oxygen sites may be doped to improve electrochemical performance. In a non-limiting example, the oxygen site is doped with fluorine. The general formula for oxygen site doping is:

[0026] Li x N y M z O 2-a F a (1)

[0027] where 1.0 < x < 1.65; 0 ≤ y < 0.55; 0.1 < z < 1; 0 ≤ a < 0.5; N is one of Ti, Ta, Zr, W, Nb or Mo; and M is one of Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Al, Zr, Y, Mo, Ru, Rh, Sn, Bi or Sb, provided that Mn is present. Other dopants such as Na and Mg can be incorporated to replace a small concentration of Li, such as 0.1% to 10% molar of Li and the dopants. These compositions have shown excellent specific capacity or energy density, such as about 350 mAh / g at 55 °C and C / 40, and about 300 mAh / g at 30 °C and C / 15. The disordered rock salt can be a rock salt with "a" being zero. Other anions can be further incorporated to replace O and / or F, as described in the co-pending application of Tanghong Yi titled "Disordered Rocksalt Material and Method of Forming" filed concurrently, which is incorporated herein by reference. Ideally, the disordered rock salt is a rock salt where N is Nb and M is Mn and Ti. When Mn and Ti are present, a Mn / Ti of 1 to 50, 25 or 10 may be desirable. When fabricating the cathode, the disordered rock salt can be mixed with other additives, thereby bringing useful properties, such as binding or improving the conductivity of the disordered rock salt powder. For example, the disordered rock salt powder can be mixed with or coated with carbon particles to increase the conductivity. Generally, the amount of carbon by weight is such that the weight ratio of disordered rock salt / carbon is 100, 50, 30, 20, 10 to about 2 or 5.

[0028] The method can produce disordered rock salts that exhibit both metal redox capacity and oxygen redox capacity, where the metal redox capacity is greater than the oxygen redox capacity. In the capacity Q (mAh / g) versus voltage V curve (voltage between about 3 V and 4.2 V), the capacity caused by the transition metal is regarded as a sloping curve from 0 to about 150 mAh / g. Thereafter, the capacity obtained on the high-voltage plateau is understood to be attributed to the oxygen anions (up to about 4.5 V). Compared with disordered rock salt cathodes not fabricated by this method, under otherwise substantially equivalent conditions, the metal redox capacity can be at least 5%, 10% or more higher than the oxygen redox capacity measured by the area under the dQ / dV curve.

[0029] It has been unexpectedly discovered that in making an improved disordered rock salt consisting of Mn, it can be made by mixing a lithium compound with a metal precursor compound consisting of Mn to form a mixture, wherein the Mn is in an oxidation state of 2. For example, the mixture consists of MnO or a mixed metal oxide, wherein at least a portion of the Mn is in an oxidation state of 2. Examples may include MnO, MnCO3, Mn3O4, Mn(NO3)2. Ideally, at least 25%, 50%, 75%, 90% to substantially all of the metal precursor compound consisting of Mn by weight present in the mixture has an Mn oxidation state of 2. The Mn precursor present in the mixture may be solely MnO.

[0030] The mixture can be formed by any suitable method such as a method known in the art, wherein U.S. Patent Publication No. 2022 / 0059816 is exemplary and incorporated herein by reference. In order to form a mixture, the metal precursor compound and the lithium compound are mixed based on the desired composition of the disordered rock salt. One or more precursors can be metal compounds composed of oxygen, fluorine and one or more P, S and N, such as oxides, hydroxides, oxynitrides, nitrides, nitrates, sulfides, sulfates, phosphates, phosphites, fluorides and combinations thereof. Examples of precursors can include Mn2O3, LiOH, Nb2O5, LiF, NbF5 and / or the like, as long as there is a sufficient amount of Mn precursors with 2 oxidation states as described above. The mixture can include one or more compounds that can introduce substituents of O or F, such as compounds with S, P, N or a combination thereof.

[0031] Mn (for example, Mn2O3) with an oxidation state greater than 2 can be formed by mixing with other metal precursor compounds, and the other metal precursor compounds may have the same stoichiometric ratio required in a part of disordered rock salt or required rock salt. When manufacturing the required disordered rock salt, a mixture of Mn compounds with an oxidation state greater than 2 and at least one other metal precursor compound can be manufactured by any suitable method such as described herein. Then this intermediate mixture can be heated to a certain temperature to form an intermediate precursor in the absence of lithium and in a certain atmosphere (for example, an inert atmosphere or an oxygen-containing atmosphere), thereby realizing a mixed metal compound, wherein at least a portion (for example, 50%, 75%, 90% to all of Mn has 2 oxidation states). If necessary, the intermediate precursor can be heated in an oxygen-containing atmosphere without lithium to form a mixed metal oxide intermediate composed of Mn with 2 oxidation states. Any useful temperature and time can be used to form an intermediate precursor. Generally, the formation of the intermediate precursor can adopt the temperature, atmosphere and holding time described for forming disordered rock salt, but ideally oxygen-free. Higher temperatures may be used if useful, but this may require further or more grinding to achieve the desired particle size when mixed with lithium compounds.

[0032] Ideally, the precursors can be mixed in a liquid (such as water or an organic solvent) in the desired amount to achieve the desired disordered rock salt stoichiometry to make a suspension (one or more precursors can be dissolved and precipitated after removing the solvent). Grinding can be carried out by any method that can be used to achieve the desired particle size, such as a micro-media mill, a planetary mill, or other comminution method (e.g., stirring, ultrasonic induction, or vibration mill). The average particle size of the particles can be up to 2 microns, 1 micron, 400 nanometers (nm), 200 nm, or 100 nm to 5 or 10 nm. An example of a suitable micro-bead mill is a Buhler PML2 mill (Buhler Group). Suitable grinding can be carried out in commercially available stirred mills such as stirred mills available from Buhler Group (Germany) and Netzsch GmbH (Germany); ultrasonic mills available from Resodyn Corporation (Butte, MT) and planetary mills available from Glen Mills Inc. (Clifton, NJ) and Retsch GmbH (Germany). Size may be determined by any suitable method, such as those known in the art including, for example, photomicrography or laser scattering.

[0033] The grinding medium can be any medium that can be used to grind ceramic particles without causing unnecessary pollution or producing a desired effect on the composition of the mixture. The grinding medium can be any useful shape, such as spherical, elliptical or cylindrical. Ideally, the grinding medium is spherical. The grinding medium can be ceramic, metal or ceramic metal composite material (such as WC / Co). The grinding medium can be any medium that can be used to grind the precursor and does not cause harmful pollution. The example of the grinding medium includes those grinding media composed of zirconium, such as cubic stable zirconia (for example, stabilized with one or more of Mg, Ca, Y, Ce, Al and Hf), zircon, silicon carbide, WC / Co, mixed carbide, such as those described in U.S. Patent No. 5,563,107 and WO2004 / 110699, which are incorporated herein by reference. Suitable cubic stable zirconia grinding media can be obtained from Chemco Advanced Material (Suzhou) Co., Ltd., China. Similarly, self-grinding such as the metal oxide required in the use composition can be used as grinding media.

[0034] The suspension of precursor particles can then be dried by any suitable method such as spray drying. Other drying methods can also be used, including evaporation, heating, vacuum application, critical fluid drying or freeze drying. Spray drying can be performed using any known commercially available spray dryer, such as a miniature spray dryer, such as the Buchi B-290 model.

[0035] The dried precursor particle mixture can then be heated to an annealing temperature. The annealing temperature causes the precursor to react and form a disordered rock salt. Ideally, the temperature and time are such that the resulting disordered rock salt does not fuse into an overall molten mass, but retains the form of a dried mixture, such as a spray-dried agglomerate of the precursor particles. The annealing temperature can be 500°C, 750°C to 900°C, 1000°C or 1200°C. The annealing temperature can be maintained for any useful time, such as 10 minutes, 1 hour, 2 hours, 3 hours or 5 hours to 12 hours or 24 hours. Surprisingly, even at a longer annealing time, the crystal growth of the mixture of the present invention is significantly inhibited compared to a mixture with only a Mn precursor having an oxidation state of 3. That is, it has been found that the particles maintain a smaller size and have improved performance, such as improved cycle life and conductivity due to a small size. In addition, since the particles can maintain a smaller size at temperature, different oxygen-containing atmospheres (i.e., oxygen partial pressures over a longer period of time, which can change during the annealing process to form a disordered rock salt) can be used to more accurately adjust the stoichiometry. For example, it may be necessary to anneal at a high temperature such as 750°C to 1200°C for a period of time in a low oxygen or oxygen-free (inert gas, such as a rare gas or nitrogen) atmosphere to form a disordered rock salt, but then reduce the temperature and anneal at a lower temperature (e.g., below 750°C to about 400°C or 500°C) in an oxygen-containing atmosphere such as air, dry air, or oxygen in nitrogen or an inert gas at any desired partial pressure. In other words, two or more annealing temperatures may be used to form a disordered rock salt. The holding time for each annealing temperature may be any time as described above.

[0036] Annealing can be carried out in any suitable atmosphere, which can be static, flowing, or a combination thereof, and can vary depending on the holding temperature employed in the method. The atmosphere can be a noble gas, nitrogen, atmospheric or dry air, and any combination thereof, to achieve the desired partial pressure of one or more gases. Annealing conditions can be selected based on the composition of the disordered rock salt precursor.

[0037] The disordered rock salt formed can be mixed by any method, wherein grinding as described herein is a suitable method for other components that can be used to make electrodes. For example, carbon can be added. Carbon can be added by a suspension and spray dried to form spray-dried particles. Carbon can include acetylene black, carbon black, carbon fiber, graphite, carbon nanotubes, KJ600 and / or the like. Carbon can be ground according to a ratio in which disordered rock salt powder accounts for the majority and carbon precursor accounts for the minority. For example, the amount of disordered rock salt and carbon each present is such that the amount of disordered rock salt / the amount of carbon by weight can be a ratio of 100 / 1, 50 / 1, 30 / 1, 20 / 1 or 10 / 1 to 5 / 1, 1.5 / or 1 / 1.

[0038] Disordered rock salt can be used to form a cathode by any suitable method such as methods known in the art. For example, disordered rock salt powder can be mixed with a binder such as a polymer (e.g., polyfluoropolymers such as polyvinylidene fluoride) and one or more solvents that can be used to make a cathode to form a slurry. Non-limiting examples of one or more solvents can be aprotic polar solvents, such as methyl-2-pyrrolidone (NMP). The slurry can then be deposited on a metal current collector (e.g., stainless steel, aluminum or any suitable conductive metal foil), and the solvent is removed to form a cathode.

[0039] Ideally, the disordered rock salt of the cathode has an average secondary particle size of at least 1 to 20 microns. Each secondary particle is an aggregate of primary particles. The DRS primary particles desirably have an average particle size as described above, and may contain other potentially useful particles, such as increasing conductivity (e.g., carbon or other inorganic high ion conductive particles).

[0040] The disordered rock salt cathode can be used in a rechargeable lithium-ion battery cell. The battery cell includes a cathode, an anode, a separator, and an electrolyte. The battery or battery cell can be formed in any suitable atmosphere, such as atmospheres common in the art. For example, a high purity argon atmosphere can be used to limit any undesirable contamination from substances present in the atmosphere.

[0041] Example

[0042] Embodiment 1:

[0043] The disordered rock salt material was synthesized in multiple steps. Typically, stoichiometric amounts of all oxide (Mn2O3, TiO2, and Nb2O5) precursors (excluding the lithium precursor) were mixed and ground in deionized water with ceramic beads in a micro-medium Buhler mill to achieve a solid suspension of about 10%, and then spray dried. The dried oxide mixture was annealed at 1000 °C for 12 hours in an inert atmosphere to form an intermediate precursor (trigonal system, R-3), in which Mn was considered to be essentially in the Mn +2 oxidation state, using black stibnite as a reference, and the X-ray diffraction pattern was shown in Figure 1 The annealed powder was mixed with lithium precursors (Li2CO3 and LiF) and ball milled for 3 h using a planetary ball mill using zirconium oxide media to prepare a mixture of lithium compounds and intermediate metal oxides, and then the mixture was annealed at 900 °C for 12 h under flowing argon to obtain a disordered rock salt phase, as shown in FIG. Figure 2 shown.

[0044] Example 2

[0045] The same stoichiometric amounts of precursors (MnO, Li2CO3, LiF, Nb2O5 and other dopants in the form of oxides or fluorides) were mixed in deionized water to form a suspension, and ball milled using a planetary ball mill in the same manner as in Example 1 to prepare a homogeneous mixture of all precursors including the lithium compound. The mixture was dried at 100°C / 12h in air and then annealed at 900°C for 12h under flowing argon to obtain a disordered rock salt.

[0046] Comparative Example 1

[0047] The same stoichiometric amounts of metal and lithium precursor were mixed in the same manner as in Example 2, but MnO was replaced by Mn2O3. Figure 3 The formation of disordered rock salt particles is shown. Figure 2 and Figure 3 It is obvious that the particle size of Example 1 is significantly smaller than that of Comparative Example 1. Figure 4 The X-ray diffraction patterns of the disordered rock salts of Example 1 and Comparative Example 1 are shown. It is obvious from the X-ray diffraction patterns that there are differences in the lattice parameters, as shown by the shift in the peak positions (see the peaks near 43° and 63° 2θ). The X-ray diffraction was measured using a Rigaku Miniflex tabletop X-ray diffractometer.

[0048] The disordered rock salt in Example 1 and the comparative example was ground with the same carbon nanotubes in a planetary ball mill with zirconium oxide media at 93:7 (powder to carbon ratio) to make the cathode. The battery cell for testing the electrochemical behavior was formed in a glove box filled with high-purity argon (M-Braun, O2 and humidity content <0.1ppm). The cathode was prepared by mixing the disordered rock salt powder with poly(vinylidene fluoride) (Sigma Aldrich) and 1-methyl-2-pyrrolidone (Sigma Aldrich) and conductive carbon to obtain a ratio of active material: carbon: PVDF = 90:7:3, and the resulting slurry was deposited on a stainless steel collector and dried to form a composite cathode film (about 2mg / cm 2 ). For the anode, thin lithium foil was cut to the required size. Each battery cell included a composite cathode membrane, a polypropylene separator and a lithium foil anode. An electrolyte (1.0M LiPF6 in EC / EMC (1:2 v / v)) was used, which contained lithium hexafluorophosphate (LiFP6) in a mixture of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) with additives. The battery cell was sealed and cycled between 1.5-4.6V at 30°C with a C / 20 formation rate and a C / 3 cycle rate, where 1C = 300 mAh / g.

[0049] The disordered rock salt of Example 1 exhibits a larger capacity from transition metal redox and a smaller capacity from oxygen anion redox. This is shown by the capacity change seen at the high voltage platform between 150 and 200 mAh / g. The capacity due to the transition metal is a sloping curve from 0 to about 150 mAh / g. Thereafter, the capacity obtained on the high voltage platform is due to oxygen anions. The disordered rock salt of Comparative Example 1 exhibits a metal redox capacity of about 130 mAh / g and an oxygen redox capacity of about 186 mAh / g, while the disordered rock salt of Example 1 exhibits a metal redox capacity of about 170 mAh / g and an oxygen redox capacity of about 120 mAh / g during initial charging. Compared to the disordered rock salt of Example 1, the larger charge capacity from anion redox for the disordered rock salt of Comparative Example 1 is clearly shown as a larger area under the peak at about 4.5 V (see the graph showing the initial charge and discharge of the batteries using the disordered rock salts of Example 1 and Comparative Example 1). Figure 5 ). The initial charge and discharge were at a C rate of C / 20. The cycle life was determined by cycling at 30 °C with charge and discharge at C / 3. The results are shown in Figure 6 , where it is apparent that the battery cell using the disordered rock salt of Example 1 shows improved cycle life compared to the battery cell using the disordered rock salt of Comparative Example 1.

Claims

1. A method, comprising: Mixing a lithium compound with a metal precursor compound composed of Mn with an oxidation state of 2 to form a mixture, and heating the mixture to a certain temperature to form a disordered rock salt.

2. The method according to claim 1, wherein the metal precursor is composed of MnO.

3. The method according to claim 1, wherein the metal precursor compound is a mixed metal oxide intermediate composed of Mn with an oxidation state of 2, and the mixed metal oxide is formed by a method comprising: Mixing a Mn compound with an oxidation state greater than 2 with at least one other metal precursor compound to a certain temperature to form an intermediate precursor mixture, And heating the intermediate precursor mixture to an intermediate temperature in an intermediate atmosphere in the absence of lithium to form a mixed metal oxide intermediate composed of Mn with an oxidation state of 2.

4. The method according to claim 3, wherein the Mn compound with an oxidation state greater than 2 is Mn2O3.

5. The method according to claim 3, wherein the intermediate atmosphere is air.

6. The method according to claim 1, wherein the heating is carried out in a substantially oxygen-free atmosphere.

7. The method according to claim 6, wherein the atmosphere is an inert gas.

8. The method according to claim 7, wherein the inert gas is a noble gas.

9. The method according to claim 6, wherein the atmosphere is composed of a flowing gas for at least a part of the heating.

10. The method according to claim 1, wherein the temperature is 800 °C to 1200 °C.

11. The method according to claim 10, wherein the temperature is maintained for a time of 10 minutes to 48 hours.

12. The method according to claim 3, wherein the intermediate temperature is 500 °C to 1200 °C.

13. The method according to claim 12, wherein the intermediate temperature is maintained for a time of 10 minutes to 24 hours.

14. The method according to claim 13, wherein the temperature is maintained at two or more different temperatures.

15. The method according to claim 1, wherein the mixing of the lithium compound and the metal precursor compound comprises grinding the lithium compound and the metal precursor compound together.

16. The method according to claim 1, wherein the disordered rock salt has the formula (i): Li x N y M z Oh 2-a F a (i) where 1.0 < x < 1.65; 0 ≤ y < 0.55; 0.1 < z < 1; 0 ≤ a < 0.5; N is one of Ti, Ta, Zr, W, Nb or Mo; M is Mn and one or more of Ti, V, Cr, Fe, Co, Ni, Cu, Zn, Al, Zr, Y, Mo, Ru, Rh, Sn, Bi or Sb.

17. A cathode composed of the disordered rock salt according to any one of the preceding claims.

18. A disordered rock salt having a metal redox capacity and an oxygen redox capacity, wherein the metal redox capacity is greater than the oxygen redox capacity.

19. The disordered rock salt according to claim 18, wherein the metal redox capacity is at least 10% greater than the oxygen redox capacity.

20. The disordered rock salt according to claim 18, wherein the disordered rock salt has the formula (i): Li x N y M z Oh 2-a F a (i) where 1.0 < x < 1.65; 0 ≤ y < 0.55; 0.1 < z < 1; 0 ≤ a < 0.5; N consists of one or more of Ti, Ta, Zr, W, Nb or Mo; M consists of Mn and one or more of Ti, V, Cr, Fe, Co, Ni, Cu, Zn, Al, Zr, Y, Mo, Ru, Rh, Sn, Bi or Sb.

21. The disordered rock salt according to claim 20, wherein "a" is zero.

22. The disordered rock salt according to claim 20 or 21, wherein N is Nb and M is Mn and Ti.

23. The disordered rock salt according to claim 22, wherein the amounts of Mn and Ti present are such that the molar ratio of Mn / Ti is from 1 to 10.

24. A cathode comprising the disordered rock salt according to any one of claims 18 to 23.

25. The cathode according to claim 24, which further comprises carbon.

26. The cathode according to claim 25, wherein the amounts of the disordered rock salt and carbon present are such that the ratio of the amount of the disordered rock salt to the amount of carbon by weight is from 100 / 1 to 1.5 / 1.

27. A composition comprising a disordered rock salt composed of Li, Mn and O, wherein at least 1 mol% of the Mn present is in the 2+ valence state.

28. The composition according to claim 27, wherein at least 10 mol% of the Mn present is in the 2+ valence state.

29. The composition according to claim 28, wherein at least 15 mol% of the Mn present is in the 2+ valence state.

30. The composition according to claim 29, wherein at least 20 mol% of the Mn present is in the 2+ valence state.

31. The composition according to claim 30, wherein at least 25 mol% of the Mn present is in the 2+ valence state.

32. The composition according to any one of claims 27 to 31, wherein the disordered rock salt has the formula (i): Li x N y M z Oh 2-a F a (i) where 1.0 < x < 1.65; 0 ≤ y < 0.55; 0.1 < z < 1; 0 ≤ a < 0.5; N consists of one or more of Ti, Ta, Zr, W, Nb or Mo; M consists of Mn and one or more of Ti, V, Cr, Fe, Co, Ni, Cu, Zn, Al, Zr, Y, Mo, Ru, Rh, Sn, Bi or Sb.